Tacrolimus-induced reversible posterior leukoencephalopathy syndrome in a child with nephrotic syndrome: a case report - Wu, Dengyan; Ma, Lina; Wu, Huimin; Li, Jie; Yang, Jing; Huang, Li (Frontiers in Pediatrics, 2026)
BackgroundTacrolimus is widely used as an immunosuppressant in the management of refractory nephrotic syndrome. Although effective, it may occasionally lead to rare but serious adverse effects such as posterior reversible leukoencephalopathy syndrome (PRES). PRES has traditionally been associated with hypertension and elevated drug concentrations.Case presentationIn the present study, we describe the case of a 10-year-old Chinese girl who was diagnosed with steroid-resistant nephrotic syndrome (SRNS) and pathologically confirmed to have minimal change nephropathy. Following 40 days of full-dose glucocorticoid therapy with inadequate improvement in proteinuria, tacrolimus was initiated at 1.5 mg twice daily (0.09 mg/kg/day). Neurological symptoms, including headache and nausea, developed 18 h after the first dose—before steady-state drug levels were reached. Within 24 h, hypertension emerged, and magnetic resonance imaging (MRI) revealed abnormal signals in the bilateral parietal cortical and subcortical regions, consistent with PRES. Tacrolimus was immediately discontinued, and the patient was treated with nifedipine, low-dose furosemide, and vitamin B6. Symptoms resolved within 48 h, and blood pressure normalized. Immunosuppressive therapy was subsequently switched to mycophenolate mofetil (MMF). Follow-up brain MRI at three months demonstrated complete resolution of the detected abnormalities.ConclusionTacrolimus-associated PRES may occur very early in treatment, even before stable drug concentrations are achieved. Vigilant clinical monitoring, prompt recognition of neurological symptoms, and timely intervention are critical to avoid long-term sequelae.